Skip to content

Commit

Permalink
corrections
Browse files Browse the repository at this point in the history
  • Loading branch information
darijgr committed May 25, 2016
1 parent f6c86d3 commit bd2f135
Showing 1 changed file with 45 additions and 40 deletions.
85 changes: 45 additions & 40 deletions sols.tex
Original file line number Diff line number Diff line change
Expand Up @@ -15,7 +15,7 @@
\usepackage{tabls}
%TCIDATA{OutputFilter=latex2.dll}
%TCIDATA{Version=5.50.0.2960}
%TCIDATA{LastRevised=Wednesday, May 25, 2016 13:06:05}
%TCIDATA{LastRevised=Wednesday, May 25, 2016 13:28:10}
%TCIDATA{SuppressPackageManagement}
%TCIDATA{<META NAME="GraphicsSave" CONTENT="32">}
%TCIDATA{<META NAME="SaveForMode" CONTENT="1">}
Expand Down Expand Up @@ -13643,11 +13643,12 @@ \subsection{Prelude to Laplace expansion}

From (\ref{eq.det.eq.2}), we obtain%
\begin{align*}
\det A & =\sum_{\sigma\in S_{n}}\left( -1\right) ^{\sigma}\underbrace{\prod
_{i=1}^{n}a_{i,\sigma\left( i\right) }}_{=\left( \prod_{i=1}^{n-1}%
a_{i,\sigma\left( i\right) }\right) a_{n,\sigma\left( n\right) }}%
=\sum_{\sigma\in S_{n}}\left( -1\right) ^{\sigma}\left( \prod_{i=1}%
^{n-1}a_{i,\sigma\left( i\right) }\right) a_{n,\sigma\left( n\right) }\\
\det A & =\sum_{\sigma\in S_{n}}\left( -1\right) ^{\sigma}%
\underbrace{\prod_{i=1}^{n}a_{i,\sigma\left( i\right) }}_{=\left(
\prod_{i=1}^{n-1}a_{i,\sigma\left( i\right) }\right) a_{n,\sigma\left(
n\right) }}=\sum_{\sigma\in S_{n}}\left( -1\right) ^{\sigma}\left(
\prod_{i=1}^{n-1}a_{i,\sigma\left( i\right) }\right) a_{n,\sigma\left(
n\right) }\\
& =\sum_{\substack{\sigma\in S_{n};\\\sigma\left( n\right) =n}}\left(
-1\right) ^{\sigma}\left( \prod_{i=1}^{n-1}a_{i,\sigma\left( i\right)
}\right) \underbrace{a_{n,\sigma\left( n\right) }}_{\substack{=a_{n,n}%
Expand All @@ -13658,7 +13659,7 @@ \subsection{Prelude to Laplace expansion}
(\ref{pf.thm.laplace.pre.1}))}}}\\
& \ \ \ \ \ \ \ \ \ \ \left( \text{since every }\sigma\in S_{n}\text{
satisfies either }\sigma\left( n\right) =n\text{ or }\sigma\left( n\right)
\neq n\text{ (but not both)}\right) \\
\neq n\text{ (but not both)}\right) \\
& =\sum_{\substack{\sigma\in S_{n};\\\sigma\left( n\right) =n}}\left(
-1\right) ^{\sigma}\left( \prod_{i=1}^{n-1}a_{i,\sigma\left( i\right)
}\right) a_{n,n}+\underbrace{\sum_{\substack{\sigma\in S_{n};\\\sigma\left(
Expand Down Expand Up @@ -13686,14 +13687,14 @@ \subsection{Prelude to Laplace expansion}
Assume that%
\begin{equation}
a_{i,n}=0\ \ \ \ \ \ \ \ \ \ \text{for every }i\in\left\{ 1,2,\ldots
,n-1\right\} .\label{eq.cor.laplace.pre.col.ass}%
,n-1\right\} . \label{eq.cor.laplace.pre.col.ass}%
\end{equation}
Then, $\det A=a_{n,n}\cdot\det\left( \left( a_{i,j}\right) _{1\leq i\leq
n-1,\ 1\leq j\leq n-1}\right) $.
\end{corollary}

\begin{proof}
[Proof of Corollary \ref{cor.laplace.pre.col}.] We have $n-1\in\mathbb{N}$
[Proof of Corollary \ref{cor.laplace.pre.col}.]We have $n-1\in\mathbb{N}$
(since $n$ is a positive integer).

We have $A=\left( a_{i,j}\right) _{1\leq i\leq n,\ 1\leq j\leq n}$, and thus
Expand All @@ -13705,7 +13706,8 @@ \subsection{Prelude to Laplace expansion}
$a_{i,j}$) yields
\begin{equation}
\det\left( A^{T}\right) =a_{n,n}\cdot\det\left( \left( a_{j,i}\right)
_{1\leq i\leq n-1,\ 1\leq j\leq n-1}\right) .\label{pf.cor.laplace.pre.col.1}%
_{1\leq i\leq n-1,\ 1\leq j\leq n-1}\right) .
\label{pf.cor.laplace.pre.col.1}%
\end{equation}


Expand Down Expand Up @@ -13736,12 +13738,12 @@ \subsection{Prelude to Laplace expansion}

Now,%
\begin{align*}
\det A & =\det\left( A^{T}\right) =a_{n,n}\cdot\underbrace{\det\left(
\det A & =\det\left( A^{T}\right) =a_{n,n}\cdot\underbrace{\det\left(
\left( a_{j,i}\right) _{1\leq i\leq n-1,\ 1\leq j\leq n-1}\right) }%
_{=\det\left( \left( a_{i,j}\right) _{1\leq i\leq n-1,\ 1\leq j\leq
n-1}\right) }\ \ \ \ \ \ \ \ \ \ \left( \text{by
(\ref{pf.cor.laplace.pre.col.1})}\right) \\
& =a_{n,n}\cdot\det\left( \left( a_{i,j}\right) _{1\leq i\leq n-1,\ 1\leq
(\ref{pf.cor.laplace.pre.col.1})}\right) \\
& =a_{n,n}\cdot\det\left( \left( a_{i,j}\right) _{1\leq i\leq n-1,\ 1\leq
j\leq n-1}\right) .
\end{align*}
This proves Corollary \ref{cor.laplace.pre.col}.
Expand Down Expand Up @@ -22050,7 +22052,10 @@ \subsection{\label{sect.desnanot}The Desnanot-Jacobi identity}

\begin{proof}
[Proof of Lemma \ref{lem.desnanot.AB.tech}.]We have $n-1\in\mathbb{N}$ (since
$n$ is a positive integer).
$n$ is a positive integer). Also, $u<v\leq n$ (since $v\in\left\{
1,2,\ldots,n\right\} $) and thus $u\leq n-1$ (since $u$ and $n$ are
integers). Combining this with $u\geq1$ (since $u\in\left\{ 1,2,\ldots
,n\right\} $), we obtain $u\in\left\{ 1,2,\ldots,n-1\right\} $.

\textbf{(a)} Let $q\in\left\{ 1,2,\ldots,n-1\right\} $. From $C=\left(
B\mid\left( I_{n}\right) _{\bullet,u}\right) $, we obtain%
Expand Down Expand Up @@ -22174,9 +22179,9 @@ \subsection{\label{sect.desnanot}The Desnanot-Jacobi identity}
\textbf{(e)} Let $A\in\mathbb{K}^{\left( n-1\right) \times n}$. Proposition
\ref{prop.addcol.props1} \textbf{(b)} (applied to $n-1$, $B$ and $\left(
I_{n}\right) _{\bullet,u}$ instead of $m$, $A$ and $v$) yields $\left(
B\mid\left( I_{n}\right) _{\bullet,u}\right) _{\bullet,\left( \left(
n-1\right) +1\right) }=\left( I_{n}\right) _{\bullet,u}$. This rewrites as
$\left( B\mid\left( I_{n}\right) _{\bullet,u}\right) _{\bullet,n}=\left(
B\mid\left( I_{n}\right) _{\bullet,u}\right) _{\bullet,\left( n-1\right)
+1}=\left( I_{n}\right) _{\bullet,u}$. This rewrites as $\left(
B\mid\left( I_{n}\right) _{\bullet,u}\right) _{\bullet,n}=\left(
I_{n}\right) _{\bullet,u}$ (since $\left( n-1\right) +1=n$). Now,
$C=\left( B\mid\left( I_{n}\right) _{\bullet,u}\right) $, so that%
\[
Expand Down Expand Up @@ -22308,7 +22313,7 @@ \subsection{\label{sect.desnanot}The Desnanot-Jacobi identity}
C_{\bullet,q}\right) }_{=\det\left( A\mid C_{\bullet,q}\right) \left(
-1\right) ^{n+q}}\det\left( C_{\sim v,\sim q}\right) =\sum_{q=1}^{n}%
\det\left( A\mid C_{\bullet,q}\right) \left( -1\right) ^{n+q}\det\left(
C_{\sim v,\sim q}\right) \\
C_{\sim v,\sim q}\right) \\
& =\sum_{q=1}^{n-1}\det\left( A\mid\underbrace{C_{\bullet,q}}%
_{\substack{=B_{\bullet,q}\\\text{(by (\ref{pf.prop.desnanot.AB.3}))}%
}}\right) \underbrace{\left( -1\right) ^{n+q}\det\left( C_{\sim v,\sim
Expand All @@ -22321,9 +22326,9 @@ \subsection{\label{sect.desnanot}The Desnanot-Jacobi identity}
\\\text{(by (\ref{pf.prop.desnanot.AB.4}))}}}\underbrace{\left( -1\right)
^{n+n}}_{\substack{=1\\\text{(since }n+n=2n\text{ is even)}}}\det\left(
\underbrace{C_{\sim v,\sim n}}_{\substack{=B_{\sim v,\bullet}\\\text{(by
(\ref{pf.prop.desnanot.AB.2}))}}}\right) \\
(\ref{pf.prop.desnanot.AB.2}))}}}\right) \\
& \ \ \ \ \ \ \ \ \ \ \left( \text{here, we have split off the addend for
}q=n\text{ from the sum}\right) \\
}q=n\text{ from the sum}\right) \\
& =\underbrace{\sum_{q=1}^{n-1}\det\left( A\mid B_{\bullet,q}\right)
\left( -\left( -1\right) ^{q+u}\det\left( \operatorname*{rows}%
\nolimits_{1,2,\ldots,\widehat{u},\ldots,\widehat{v},\ldots,n}\left(
Expand All @@ -22332,18 +22337,18 @@ \subsection{\label{sect.desnanot}The Desnanot-Jacobi identity}
\operatorname*{rows}\nolimits_{1,2,\ldots,\widehat{u},\ldots,\widehat{v}%
,\ldots,n}\left( B_{\bullet,\sim q}\right) \right) }\\
& \ \ \ \ \ \ \ \ \ \ +\left( -1\right) ^{n+u}\det\left( A_{\sim
u,\bullet}\right) \det\left( B_{\sim v,\bullet}\right) \\
u,\bullet}\right) \det\left( B_{\sim v,\bullet}\right) \\
& =-\sum_{q=1}^{n-1}\left( -1\right) ^{q+u}\det\left( A\mid B_{\bullet
,q}\right) \det\left( \operatorname*{rows}\nolimits_{1,2,\ldots
,\widehat{u},\ldots,\widehat{v},\ldots,n}\left( B_{\bullet,\sim q}\right)
\right) \\
\right) \\
& \ \ \ \ \ \ \ \ \ \ +\left( -1\right) ^{n+u}\det\left( A_{\sim
u,\bullet}\right) \det\left( B_{\sim v,\bullet}\right) .
\end{align*}
Adding $\sum_{q=1}^{n-1}\det\left( A\mid B_{\bullet,q}\right) \det\left(
\operatorname*{rows}\nolimits_{1,2,\ldots,\widehat{u},\ldots,\widehat{v}%
,\ldots,n}\left( B_{\bullet,\sim q}\right) \right) $ to both sides of this
equality, we obtain%
Adding $\sum_{q=1}^{n-1}\left( -1\right) ^{q+u}\det\left( A\mid
B_{\bullet,q}\right) \det\left( \operatorname*{rows}\nolimits_{1,2,\ldots
,\widehat{u},\ldots,\widehat{v},\ldots,n}\left( B_{\bullet,\sim q}\right)
\right) $ to both sides of this equality, we obtain%
\begin{align*}
& \sum_{q=1}^{n-1}\left( -1\right) ^{q+u}\det\left( A\mid B_{\bullet
,q}\right) \det\left( \operatorname*{rows}\nolimits_{1,2,\ldots
Expand All @@ -22358,7 +22363,7 @@ \subsection{\label{sect.desnanot}The Desnanot-Jacobi identity}
& \sum_{q=1}^{n-1}\left( -1\right) ^{q+u}\det\left( A\mid B_{\bullet
,q}\right) \det\left( \operatorname*{rows}\nolimits_{1,2,\ldots
,\widehat{u},\ldots,\widehat{v},\ldots,n}\left( B_{\bullet,\sim q}\right)
\right) \\
\right) \\
& =\left( -1\right) ^{n+u}\det\left( A_{\sim u,\bullet}\right)
\det\left( B_{\sim v,\bullet}\right) -\det\left( A_{\sim v,\bullet}\right)
\underbrace{\det C}_{\substack{=\left( -1\right) ^{n+u}\det\left( B_{\sim
Expand All @@ -22370,7 +22375,7 @@ \subsection{\label{sect.desnanot}The Desnanot-Jacobi identity}
\\
& =\left( -1\right) ^{n+u}\det\left( A_{\sim u,\bullet}\right)
\det\left( B_{\sim v,\bullet}\right) -\left( -1\right) ^{n+u}\det\left(
A_{\sim v,\bullet}\right) \det\left( B_{\sim u,\bullet}\right) \\
A_{\sim v,\bullet}\right) \det\left( B_{\sim u,\bullet}\right) \\
& =\left( -1\right) ^{n+u}\left( \det\left( A_{\sim u,\bullet}\right)
\det\left( B_{\sim v,\bullet}\right) -\det\left( A_{\sim v,\bullet}\right)
\det\left( B_{\sim u,\bullet}\right) \right) .
Expand All @@ -22381,13 +22386,13 @@ \subsection{\label{sect.desnanot}The Desnanot-Jacobi identity}
& \left( -1\right) ^{u}\sum_{q=1}^{n-1}\left( -1\right) ^{q+u}\det\left(
A\mid B_{\bullet,q}\right) \det\left( \operatorname*{rows}%
\nolimits_{1,2,\ldots,\widehat{u},\ldots,\widehat{v},\ldots,n}\left(
B_{\bullet,\sim q}\right) \right) \\
B_{\bullet,\sim q}\right) \right) \\
& =\underbrace{\left( -1\right) ^{u}\left( -1\right) ^{n+u}%
}_{\substack{=\left( -1\right) ^{u+\left( n+u\right) }=\left( -1\right)
^{n}\\\text{(since }u+\left( n+u\right) =2u+n\equiv n\operatorname{mod}%
2\text{)}}}\left( \det\left( A_{\sim u,\bullet}\right) \det\left( B_{\sim
v,\bullet}\right) -\det\left( A_{\sim v,\bullet}\right) \det\left( B_{\sim
u,\bullet}\right) \right) \\
u,\bullet}\right) \right) \\
& =\left( -1\right) ^{n}\left( \det\left( A_{\sim u,\bullet}\right)
\det\left( B_{\sim v,\bullet}\right) -\det\left( A_{\sim v,\bullet}\right)
\det\left( B_{\sim u,\bullet}\right) \right) ,
Expand All @@ -22396,21 +22401,21 @@ \subsection{\label{sect.desnanot}The Desnanot-Jacobi identity}
\begin{align*}
& \left( -1\right) ^{n}\left( \det\left( A_{\sim u,\bullet}\right)
\det\left( B_{\sim v,\bullet}\right) -\det\left( A_{\sim v,\bullet}\right)
\det\left( B_{\sim u,\bullet}\right) \right) \\
\det\left( B_{\sim u,\bullet}\right) \right) \\
& =\left( -1\right) ^{u}\sum_{q=1}^{n-1}\left( -1\right) ^{q+u}%
\det\left( A\mid B_{\bullet,q}\right) \det\left( \operatorname*{rows}%
\nolimits_{1,2,\ldots,\widehat{u},\ldots,\widehat{v},\ldots,n}\left(
B_{\bullet,\sim q}\right) \right) \\
B_{\bullet,\sim q}\right) \right) \\
& =\sum_{q=1}^{n-1}\underbrace{\left( -1\right) ^{u}\left( -1\right)
^{q+u}}_{\substack{=\left( -1\right) ^{u+\left( q+u\right) }=\left(
-1\right) ^{q}\\\text{(since }u+\left( q+u\right) =2u+q\equiv
q\operatorname{mod}2\text{)}}}\det\left( A\mid B_{\bullet,q}\right)
\det\left( \operatorname*{rows}\nolimits_{1,2,\ldots,\widehat{u}%
,\ldots,\widehat{v},\ldots,n}\left( B_{\bullet,\sim q}\right) \right) \\
,\ldots,\widehat{v},\ldots,n}\left( B_{\bullet,\sim q}\right) \right) \\
& =\sum_{q=1}^{n-1}\left( -1\right) ^{q}\det\left( A\mid B_{\bullet
,q}\right) \det\left( \operatorname*{rows}\nolimits_{1,2,\ldots
,\widehat{u},\ldots,\widehat{v},\ldots,n}\left( B_{\bullet,\sim q}\right)
\right) \\
\right) \\
& =\sum_{r=1}^{n-1}\left( -1\right) ^{r}\det\left( A\mid B_{\bullet
,r}\right) \det\left( \operatorname*{rows}\nolimits_{1,2,\ldots
,\widehat{u},\ldots,\widehat{v},\ldots,n}\left( B_{\bullet,\sim r}\right)
Expand Down Expand Up @@ -49289,8 +49294,8 @@ \subsection{Solution to Exercise \ref{exe.prop.addcol.props}}
\begin{proof}
[Proof of Proposition \ref{prop.addcol.props3}.]\textbf{(a)} Proposition
\ref{prop.addcol.props3} \textbf{(a)} simply says that if we remove the $n$-th
column from the matrix $A$, and then reattach this column back to $A$ (at its
right edge), then we get the original matrix $A$ back. This should be
column from the matrix $A$, and then reattach this column back to the matrix
(at its right edge), then we get the original matrix $A$ back. This should be
completely obvious\footnote{Nevertheless, let me give a formal proof of
Proposition \ref{prop.addcol.props3} \textbf{(a)} as well:
\par
Expand Down Expand Up @@ -49378,8 +49383,8 @@ \subsection{Solution to Exercise \ref{exe.prop.addcol.props}}
\ref{prop.addcol.props3} \textbf{(b)}: Let $q\in\left\{ 1,2,\ldots,n\right\}
$. The matrix $\left( A_{\bullet,\sim q}\mid A_{\bullet,q}\right) $ is
obtained from the matrix $A$ by removing the $q$-th column and then
reattaching this column to the right end of the matrix $A$. This procedure can
be replaced by the following procedure, which clearly leads to the same result:
reattaching this column to the right end of the matrix. This procedure can be
replaced by the following procedure, which clearly leads to the same result:

\begin{itemize}
\item Switch the $q$-th column of $A$ with the $\left( q+1\right) $-th column;
Expand Down Expand Up @@ -50677,8 +50682,8 @@ \subsection{Solution to Exercise \ref{exe.prop.addcol.props}}
\ref{prop.addcol.props3} \textbf{(b)}: Let $q\in\left\{ 1,2,\ldots,n\right\}
$. The matrix $\left( A_{\bullet,\sim q}\mid A_{\bullet,q}\right) $ is
obtained from the matrix $A$ by removing the $q$-th column and then
reattaching this column to the right end of the matrix $A$. This procedure can
be replaced by the following procedure, which clearly leads to the same result:
reattaching this column to the right end of the matrix. This procedure can be
replaced by the following procedure, which clearly leads to the same result:

\begin{itemize}
\item Switch the $q$-th column of $A$ with the $\left( q+1\right) $-th column;
Expand Down

0 comments on commit bd2f135

Please sign in to comment.